La història de Teòfil d’Adana: edició crítica de la traducció catalana - Perujo Melgar, Joan M. (2023)
A study and edition of the anonymous Catalan translation of the history of Theophilus of Adana, translated in the fourteenth century from the ninth-century Latin version of Paul the Deacon of Naples, who in turn translated its sixth-century Greek original. The Catalan text has been preserved in the Real Biblioteca del Monasterio de El Escorial Library Ms M-II-3, dated in the first third of the fifteenth century, which also includes a life of Saint Mary of Egypt belonging to the same tradition. The work includes the pact with the devil topic (M210-219 of the Thompson’s index and 3566-3572 of Tubach’s), of long-enduring artistic and literary fame, running through the Middle Ages in diverse literary genres and culminating in the myth of Faust as treated by Marlowe and Goethe. This Catalan translation and the Latin tradition from which it derives are analysed. The study includes the critical edition of the Catalan text, previously unpublished, annotated from the Latin text edited by Meersseman (1963) and Ms Thott 128 of the Royal Library of Copenhagen, closer to the underlying model followed by the Catalan translator, representing, in turn, the universal collection of miracles that Gonzalo de Berceo must have used as a source in the Milagros de Nuestra Señora.
Keywords: Crítica textual; Traducción; Mitología